A treasure trove of endemics: two new species of snake-eyed skinks of the genus Panaspis Cope, 1868 (Squamata: Scincidae) from the Serra da Neve Inselberg, southwestern Angola - Marques, Mariana P.; Parrinha, Diogo; Lopes-Lima, Manuel; Tiutenko, Arthur; Bauer, Aaron Matthew; Ceríaco, Luís Miguel Pires (Evolutionary Systematics, 2024)
Four species of the genus Panaspis – P. cabindae, P. wahlbergi, P. maculicollis and P. mocamedensis – are currently known from Angola. The analysis of recently collected specimens from Serra da Neve Inselberg, an isolated mountain located in northern Namibe Province, revealed unexpected taxonomic diversty in the group. Using an integrative taxonomy approach based on morphological and DNA sequence data, with both mitochondrial (16S) and nuclear (RAG-1) genes, we were able to distinguish two distinct populations, described here as two new species, Panaspis ericae sp. nov. and P. mundavambo sp. nov. Both species are assumed to be endemic to the inselberg. This reinforces our notion of southwestern Angola as a hotspot of skink diversity, and highlights the urgent need for the conservation of Serra da Neve.<br
Keywords: reptiles; integrative taxonomy; Africa; herpetofauna; cryptic species